Prolonged sitting in office environments: A scoping review of assessment methods. - Behzad, Adele; Kim, Eunsik; Chung, Joon (Work, 2026)
Background: Prolonged sitting in office environments is a major contributor to musculoskeletal disorders (MSDs), representing a growing concern for occupational health and ergonomics. Objective: This scoping review aimed to examine the range of methods used to assess sitting postures among office workers, emphasizing their applications, strengths, and limitations. Methods: A comprehensive search identified 42 studies published between 2000 and December 2023 from an initial pool of 167 articles. Studies were categorized into self-assessment, observational, and instrument-based approaches following PRISMA-ScR guidelines. Results: Self-assessment methods were the most common (69.05%), capturing subjective reports of discomfort, followed by observational tools (38.09%) for postural risk evaluation and instrument-based approaches (45.24%) utilizing sensor- and vision-based technologies for objective analysis. Several studies combined two or more methods to improve data validity through cross-validation and to achieve a more comprehensive understanding of posture-related risks. Conclusions: This review synthesizes current approaches for evaluating sitting postures in office settings and highlights methodological trends, gaps, and opportunities to guide future ergonomic research aimed at reducing MSD risks.